How does motivational interviewing work? Therapist interpersonal skill predicts client involvement within motivational interviewing sessions - Moyers, Theresa B; Miller, William R; Hendrickson, Stacey M L (Journal of consulting and clinical psychology, 2005)
Although many studies have shown that motivational interviewing (MI) is effective in reducing problem behaviors, few have investigated purported causal mechanisms. Therapist interpersonal skills have been proposed as an influence on client involvement during MI sessions and as a necessary precursor to client commitment language. Using the Motivational Interviewing Skills Code (MISC; Version 1.0) rating system, the authors investigated 103 unique MI sessions for substance abuse and found that therapist interpersonal skills were positively associated with client involvement as defined by cooperation, disclosure and expression of affect. An unexpected finding indicated that behaviors inconsistent with MI enhanced the impact of therapist interpersonal skills upon client involvement. Drawbacks to the study include a potential sampling bias and uneven reliability of the variables measured.